Ultrasound‐Assisted Precise In Situ Decompression for Cubital Tunnel Syndrome - Jin‐mei Gao; Yu Yuan; Ke‐tong Gong; Xin‐long Ma; Xin Chen (Orthopaedic Surgery, 2021)
Objective To explore the effect of locating the ulnar nerve compression sites and guiding the small incision so as to decompress the ulnar nerve in situ on the elbow by high‐frequency ultrasound before operation. Methods A retrospective analysis was conducted on 56 patients who underwent ultrasound‐assisted in situ decompression for cubital tunnel syndrome from May 2018 to August 2019. The patients' average age was 51.13 ± 7.35 years, mean duration of symptoms was 6.51 ± 1.96 months, and mean postoperative follow‐up was 6.07 ± 0.82 months. Nine patients had Dellon's stage mild, 39 had stage moderate, and eight had stage severe. Ultrasound and electromyography were completed in all patients before operation. The presence of ulnar nerve compressive lesion, the specific location, and the reason and extent of compression were determined by ultrasound. A small incision in situ surgery was given to decompress the ulnar nerve according to the pre‐defined compressive sites. Results All patients underwent in situ decompression. The compression sites around the elbow were as follows: two in the arcade of Struthers, one in the medial intermuscular septum, four in the anconeus epitrochlearis muscle, five beside the cyst of the proximal flexor carpi ulnaris (FCU), and the remaining 44 cases were all from the compression between Osborne's ligament to the two heads of the FCU. The compression localizations diagnosed by ultrasound were confirmed by operations. Preoperative ultrasound confirmed no ulnar nerve subluxation in all cases. The postoperative outcomes were satisfactory. There was no recurrence or aggravation of symptoms in this group of patients according to the modified Bishop scoring system; results showed that 43 cases were excellent, 10 were good, and three were fair. Conclusions High‐frequency ultrasound can accurately and comprehensively evaluate the ulnar nerve compression and the surrounding tissues, thus providing significant guidance for the precise minimally invasive treatment of ulnar nerve compression.